Bioavailability of Rapeseed Oil Fortified with Ethyl Sinapate - Dobrochna Rabiej-Kozioł; Marek P. Krzemiński; Iwona Wiśniewska; Aleksandra Szydłowska-Czerniak (Chemistry Proceedings, 2021)
In recent years, phenolic acid esters have been proposed as valuable additives in the food and cosmetic industries. Therefore, ethyl sinapate (ESA) was synthesized using an enzymatic approach. Hence, the bioaccessibility of antioxidant compounds after the in vitro digestion process of rapeseed oil fortified with ESA was evaluated. The antioxidant activity (AA) of the oil samples before and after digestion was analyzed using three spectrophotometric methods. The addition of synthesized ESA at concentrations of 0.02 and 0.5% caused a two- to ten-fold increase in the AA of the rapeseed oils. Therefore, the obtained phenolipid can be used as an efficient antioxidant in the oil industry.